1993
DOI: 10.1002/lsm.1900130505
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic activity of liposome‐delivered Cd‐texaphyrin using tumor‐bearing nude mice

Abstract: Photodynamic effects in bladder-tumor bearing nude mice induced by a krypton ion laser (752.5 nm) after i.v. application of liposome-delivered cadmium texaphyrin were investigated. Cd-texaphyrin possesses strong absorption transitions in the far red spectral region (around 760 nm) and a high quantum efficiency of singlet oxygen production. No therapeutic effects were obtained using irradiation 24 hours after administration of the sensitizer, whereas phototreatment 2 hours after application led to significant t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
1
4
1
Order By: Relevance
“…It also could be the result of more efficient production of singlet oxygen by PCI-0123 [7,29], which would lead to greater cytotoxicity at the drug localization site. Our finding of greater efficacy with PCI-0123 than with Photofrin is opposite to that found by Konig et al [13] when comparing Cd-texaphyrin with hematoporphyrin derivative. The most likely explanation of this difference is that the metal species in the center of the texaphyrin moiety affects the usefulness of that particular texaphyrin compound as a photosensitizer.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…It also could be the result of more efficient production of singlet oxygen by PCI-0123 [7,29], which would lead to greater cytotoxicity at the drug localization site. Our finding of greater efficacy with PCI-0123 than with Photofrin is opposite to that found by Konig et al [13] when comparing Cd-texaphyrin with hematoporphyrin derivative. The most likely explanation of this difference is that the metal species in the center of the texaphyrin moiety affects the usefulness of that particular texaphyrin compound as a photosensitizer.…”
Section: Discussioncontrasting
confidence: 99%
“…This study, like those of Young et al [8], Konig et al [13], and Woodburn et al [14,16], found that early light application times, 5-6 hr after drug injection, were most effective. The diminished PDT response at 24 hr after drug administration and the observation that the urine color had returned to normal by that time indicates that most of the unbound photosensitizer had cleared from the animals by that time.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The strong SOC effect of heavy metal atoms makes the transition metal complexes possess great advantages over organic compounds in ISC between the spin-forbidden states. In fact, some diamagnetic metals, such as Lu, Hg, Cd, and Zn, are known to enhance ISC and to elongate triplet lifetime of the PS. , Instead, the paramagnetic ones are found to deactivate the excited state, reduce the excited-state lifetime, and prevent the occurrence of photochemical reactions . Among these diamagnetic metal complexes, the Zn-containing complexes remain widely used as PDT candidates due to their richly populated triplet excited states and efficient photodynamic production of singlet oxygen. ,, The electron configurations of Zn ion are elucidated in detail to find the reason why Zn complexes are so popularly applied in PDT.…”
Section: Introductionmentioning
confidence: 99%